2021
DOI: 10.1007/s00424-021-02621-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased β-adrenergic stimulation augments vascular smooth muscle cell calcification via PKA/CREB signalling

Abstract: In chronic kidney disease (CKD), hyperphosphatemia promotes medial vascular calcification, a process augmented by osteogenic transdifferentiation of vascular smooth muscle cells (VSMCs). VSMC function is regulated by sympathetic innervation, and these cells express α- and β-adrenergic receptors. The present study explored the effects of β2-adrenergic stimulation by isoproterenol on VSMC calcification. Experiments were performed in primary human aortic VSMCs treated with isoproterenol during control or high pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Moreover, in hyperphosphatemia, vascular smooth muscle cells tend to differentiate into a synthetic phenotype, promoting calcification within the medial wall. 14,16,[29][30][31] The binding of osteocalcin to hydroxyapatite further contributes to hydroxyapatite deposition and subsequent calcification. 32,33 Previous studies have suggested a relationship between CKD and the CAC severity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in hyperphosphatemia, vascular smooth muscle cells tend to differentiate into a synthetic phenotype, promoting calcification within the medial wall. 14,16,[29][30][31] The binding of osteocalcin to hydroxyapatite further contributes to hydroxyapatite deposition and subsequent calcification. 32,33 Previous studies have suggested a relationship between CKD and the CAC severity.…”
Section: Discussionmentioning
confidence: 99%
“…The HAoSMCs were treated with equal amounts of the vehicle as a control. HAoSMCs were transfected with 10 nM POSTN (ID: s20888) or negative control (ID: 4390843) siRNA using a siPORT amine transfection reagent (all from Fisher Scientific, Vienna, Austria) [ 33 ]. For the calcification experiments, the HAoSMCs were treated for 11 days with 10 mM β-glycerophosphate and 1.5 mM CaCl 2 (Sigma Aldrich, Vienna, Austria) as a calcification medium [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…The mice were injected with colchicine, a microtubule disrupting agent, on each side of the hippocampus, and its learning and memory ability decreases obviously, the pathological examination showed colchicine selective destruction of particle vertebral body cell nucleus, hippocampus neurons induced deformation of fiber, choline acetyltransferase fell, the morphology of neurons apoptosis characteristics, similar to the AD pathology performance. Isoproterenol can activate PKA, after the bilateral hippocampus of rats is injected with isoproterenol, the symptoms of Tau protein hyperphosphorylation will appear, and memory impairment and the level of oxidative stress will increase after 48 h (Moser et al., 2021). Other drugs, such as O‐GlcNAcylation and haloperidol, can be used as inducers to induce Tau hyperphosphorylation (Huang et al., 2020; Koppel et al., 2016).…”
Section: Ad Animal Modelmentioning
confidence: 99%